Optimising honeybee (Apis mellifera scutellata: Lepeletier) performance in laboratory conditions : effects of diet state, cage volume and bee density on survival and nutrient regulation - Nicolson, Sue W. (2026)
Dissertation (MSc (Entomology))--University of Pretoria, 2017.